Effect of Dietary Protein and Peptide in Corn-Soy Diets on Hen Performance,Egg Solids, Egg Composition and Egg Quality of Hy-Line W- 36 Hens During Second Cycle Phase Three - Gunawardana, P.; Wu, G.; Yuan, Kun; Bryant, M.M.; Roland, Sr., D.A. (International Journal of Poultry Science, 2009)
A 5 x 2 factorial arrangement of five protein levels with and without Peptiva was conducted to evaluate the effect of Peptiva on performance, egg composition, egg solids, and egg quality of commercial Leghorns. Hy-line W-36 hens (n=1200, 98 weeks old) were randomly divided into 10 dietary treatments (8 replicates of 15 hens per treatment). The experiment lasted 12 weeks. Protein had a significant effect on feed consumption, egg weight, egg production, egg mass, egg specific gravity, egg albumen solids, and percent egg components. As dietary protein increased from 13.53 to 15.62%, egg production, feed consumption and egg weight increased by 6.14%, 8.2% and 5.18% respectively. Feed consumption of hens fed the diets supplemented with Peptiva was significantly lower than that of hens fed the diets without Peptiva. Peptiva supplementation also significantly increased egg production of hens during week 98 and numerically higher in week 99, 103, 105, 106, 107, 109 and overall egg production. There was also a significant effect of peptiva on egg mass and feed conversion during first week but the significant effects were lost after second week.Peptiva significantly decreased feed intake without causing any adverse effects on egg weight and egg production. eptiva might be more beneficial for young hens. More research is needed with oung hens to evaluate performance and profits of commercial layers at different egg and ingredient prices.